Analisis Pengendalian Kualitas Jerrycan Plastik Dengan Metode FTA Dan FMEA Pada Departement Moulding Di PT. PHPO - Ismarialdi; Bonar Harahap; Tri Hernawati (Industrika : Jurnal Ilmiah Teknik Industri, 2023)
PT Permata Hijau Palm Oleo (PHPO) is one of the producers in the manufacturing industry that produces plastic jerrycan as cooking oil packaging. At this time, based on the data that researchers obtained during November 2022, the company has jerrycan product quality problems. There were rejects amounting to 21,134 Pcs (3%) of the total production of 637,128 pcs. The types of rejects that occur are reject topload test, droptest, brimfull test, parting line and visual defects. Based on pareto chart analysis, it is obtained that reject topload test with a weight of 42% and reject droptest products with a weight of 32%, therefore an analysis will be carried out to improve the two types of reject products using the fault tree analysis (FTA) method, it is obtained that the root causes of reject topload test and droptest products are influenced by human factors, machines and raw materials. Things that can be done to improve the reject process topload test and droptest using the RPN (Risk Priority Number) value based on FMEA (Failure Mode and Effect Analysis) analysis, namely by cleaning the diehied from the remaining material and performing regular maintenance on the Ellement Heater section to avoid damage so that it will affect the extruder temperature.Keywords: FMEA, FTA, Jerrycan, Pareto Chart, Quality